Cost and Time Variance Analysis Using The Earned Value Method: A Case Study of The Laju Lor Village Drainage Channel Construction Project In Tuban Regency - Utuh Dwi Candra Kelana Putra; Hanie Teki Tjendani; Budi Witjaksana (International Journal Labs, 2025)
This study aims to analyze the performance of the Drainage Development project in Laju Lor Village, Tuban District, using the Earned Value Management (EVM) method. The method integrates time and cost concepts through three main indicators: ACWP (Actual Cost of Work Performed), BCWP (Budgeted Cost of Work Performed), and BCWS (Budgeted Cost of Work Schedule). The research focuses on calculating Cost Variance (CV) and Schedule Variance (SV) to evaluate project performance. The method was applied to track the project's performance over a period of 5 weeks. In week 1, the project showed a delay of 0.38%, which increased to 4.84% by week 2. By the end of week 5, the results revealed that the Schedule Variance (SV) was Rp 74,378,242.82 (-), indicating that the project was behind schedule, while the Cost Variance (CV) was Rp 20,726,358.11 (+), showing that the costs incurred were less than the budgeted amount. The findings highlight the importance of using the Earned Value method to monitor project performance, ensuring that deviations in schedule and costs are promptly identified and addressed. The study concludes that implementing efficient control mechanisms and consistent supervision is essential for mitigating delays and improving project performance, specifically for the Laju Lor Village Drainage construction project in Tuban Regency. The research provides valuable insights for construction service providers to enhance project management practices and avoid further delays.